The Alternative way to estimate the global solar radiation in Sabha city in southern Libya - Abdalraheem, Ali; Omar, Baba (Journal of Earth Energy Engineering, 2024)
In Libya some climatic parameters without solar radiation data are measured at meteorological stations. In south of Libya where the most solar energy available, there is no recorder data any more. Because of equipment installation, repair costs, poor maintenance culture and recent events in Libya. This study aims to estimate the global solar radiation in the city of Sabha in southern Libya. Data used in this purpose is the average monthly daily values of sunshine hours for previous years (2000 - 2010). The data were obtained from the archive of the meteorological station at Sabha airport. A model based on the hours of sunshine is used to calculate the horizontal solar radiation in the city. Calculated values are compared with other measurement data from NASA website. The comparisons are made using standard statistical tests, namely root mean square error (RMSE), mean bias error (MBE) and the correlation coefficient R. Statistical analysis: the RMSE average value in all years is positive and small (0.42), which make it desirable. The MBE average value in all years has negative value (-0.10), which is under estimation. Finally, the correlation coefficient R, the correlation between the estimated values and the measured values from NASA is a positive correlation in all years, reaching (0.9) and the correlation strength is strong. It may almost reach complete correlation.